2021
DOI: 10.1186/s12879-021-06561-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of patients with central nervous system infections, mainly neurosurgical patients: a retrospective study from 2012 to 2019 in a teaching hospital in China

Abstract: Background Central nervous system (CNS) infections are relatively rare but are associated with high mortality worldwide. Empirical antimicrobial therapy is crucial for the survival of patients with CNS infections, and should be based on the knowledge of the pathogen distribution and antibiotic sensitivities. The aim of this study was to investigate the features of pathogens in patients with CNS infections in North China and evaluate the risk factors for mortality and multi-drug-resistant (MDR) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 44 publications
(67 reference statements)
1
9
0
Order By: Relevance
“…This finding is consistent with another observational study conducted in Malaysia where tuberculous meningitis was not only the most diagnosed CNS infection, but also a cause of significant mortality and morbidity among the patients 5 . The male: female ratio in our study was 1.43:1 which is in line with the finding of a study done in China 12 (3:1) but in contrast to the global data obtained from a comprehensive meta‐analysis (1:1.74) 1 . Almost half of the patients were from Province 3 (Bagmati), and the location of our institution in the same province explains this data.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with another observational study conducted in Malaysia where tuberculous meningitis was not only the most diagnosed CNS infection, but also a cause of significant mortality and morbidity among the patients 5 . The male: female ratio in our study was 1.43:1 which is in line with the finding of a study done in China 12 (3:1) but in contrast to the global data obtained from a comprehensive meta‐analysis (1:1.74) 1 . Almost half of the patients were from Province 3 (Bagmati), and the location of our institution in the same province explains this data.…”
Section: Discussionsupporting
confidence: 93%
“…Collectively, these findings suggest that aging microglia are hyperinflammatory, both at baseline and in response to bacterial stimuli due, in part, to changing methylation landscapes. This is an epigenetic phenomenon that could play a key role in explaining increased CNS infection susceptibility and poor outcomes in the elderly 42 . An ongoing clinical analysis in our laboratory appears to agree with this possibility, where increased age was associated with a greater‐than‐average risk of surgical‐site infection following a craniotomy neurosurgical intervention (unpublished data).…”
Section: First Responders To Cns Infectionmentioning
confidence: 61%
“…This is an epigenetic phenomenon that could play a key role in explaining increased CNS infection susceptibility and poor outcomes in the elderly. 42 An ongoing clinical analysis in our laboratory appears to agree with this possibility, where increased age was associated with a greater‐than‐average risk of surgical‐site infection following a craniotomy neurosurgical intervention (unpublished data). This association is correlative at present, but skewed microglial epigenetic regulation may represent an important factor for promoting CNS infection risk in aging populations.…”
Section: First Responders To Cns Infectionmentioning
confidence: 79%
“…Shi et al and Zhang et al reported that age > 50 years, MV, ICU admission, pulmonary infections, and GCS score ≤ 8 were risk factors for increased mortality, whereas CSF information, operative data, and mNGS testing were not evaluated in their studies. [ 13 , 14 ] Our study revealed that in addition to GCS score, MV, and age, C/B-Glu ≤ 0.23, a total number of operations larger than 2 and non-mNGS test were also risk factors for mortality. In the Cox proportional hazards analysis, we found that MV and poor wound healing were significant risk factors for mortality.…”
Section: Discussionmentioning
confidence: 75%